The Lynching of Witches in Northern Ghana - Samuel Kofi Boateng Nkrumah-Pobi (African Theological Journal for Church and Society)
Witchcraft accusations and maltreatment have become a menace in the northern part of Ghana. Most of the people who were accused of being witches are women, children, and the poor in the society. In these parts of the country, some camps have been set up as a haven for these accused persons, so as not to incur the wrath of their family and society. Despite the existence of these camps, in 2020, a ninety-year-old woman by the name of Akua Denteh was lynched to death for being accused of witchcraft. This was against the backdrop of a traditional priestess accusing her of being a witch. In a video that circulated online on various social media platforms, one could identify a young woman and an elderly woman molesting and beating the ninety-year-old woman in the glare of the public. This act is usually referred to as mob justice in Ghana. This is an act whereby a mob, most often numbering several dozens or hundreds, takes the law into their own hands to cause harm and kill a person who has done or is accused of doing a wrong act. In this act, the issue of the victims’ status is most often secondary, since the mob acts as a prosecutor, judge, jury, and executioner. Thus, employing a feminist public theological perspective, this study interrogates the traditional institution of witch camps and the accusation of women being witches in northern Ghana. This study would use the lynching of a ninety-year-old woman as a case study. This study notes that the church is comfortable with the notion of witches’ camps, which they argue is a haven for these accused women, rather than fighting against the evils of these cultural practices. This paper argues that the church must engage the public as a prophetic voice of action to bring to an end this gender-based injustice, which does not promote life.